The effect of buckle closure and temperature on the in-vivo flexibility of ski-boots: A pilot study - Petrone, N.; Marcolin, G.; Cognolato, M.; Hofer, P.; Nachbauer, W. (Procedia Engineering, 2014)
Stiffness properties of ski-boots in forward/backward flexion are fundamental in characterizing their level of performance considering that they have to transmit control loads from the skier to the skis. Despite their importance, the mechanical characterization of the ski-boots still lacks of a standardized laboratory method. Ski-boot behavior can be influenced by several factors in addition to their construction, such as buckles level of closure and environmental temperature.